Intimacy and Smartphone Multitasking—A New Oxymoron?. Issue 3 (December 2016) - Amichai-Hamburger, Yair; Etgar, Shir
This study investigated the relationship between smartphone multitasking and romantic intimacy. Participants currently in a romantic relationship ( N = 128; 98 women; M age = 26.7 years, SD = 4.3) filled out two sets of questionnaires: The Emotional Intimacy Scale, measuring romantic intimacy, and the mobile phone interference in life scale, measuring multitasking on a smartphone. Participants filled out each questionnaire twice, once in relation to themselves and once in relation to their partner (for the partner questionnaire, statements were altered from the first person to the third person singular, he/she instead of I ). Results suggested that only the partners' smartphone multitasking scores were negatively related to ratings of romantic intimacy, whereas participants' own smartphone multitasking scores were not related to ratings of romantic intimacy. These results can be explained by the actor–observer asymmetry, suggesting that participants attributed their multitasking behaviors to situations, but attributed their partners multitasking behaviors to behavior patterns or intentionality. This research suggests that smartphone multitasking has a negative association with face-to-face interactions. People should attend to the costs of smartphone use during face-to-face interactions.